2021
DOI: 10.1016/j.eclinm.2021.101134
|View full text |Cite
|
Sign up to set email alerts
|

The association between CD8+ tumor-infiltrating lymphocytes and the clinical outcome of cancer immunotherapy: A systematic review and meta-analysis

Abstract: Background The responses of cancer patients to immune checkpoint inhibitors (ICIs) vary in success. CD8+ tumor infiltrating lymphocytes (TILs) play a key role in killing tumor cells. This study aims to evaluate the prognostic role of CD8+ TILs in cancer patients treated with ICIs. Methods We systematically searched all publications from PubMed, EMBASE, and Cochrane Library until 12 Jul 2021 without any restriction of language or article types. Studies assessing high ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 77 publications
12
106
1
1
Order By: Relevance
“…Although tumor tissue-based efficacy biomarkers of immune checkpoint inhibitors (ICIs), such as tumor-infiltrating lymphocyte counts and PD-1/PD-L1 expression, have been reported in a variety of cancer types [ 9 , 10 ], there is no reliable biomarker for predicting the efficacy of combination immunotherapy in HCC. Furthermore, because advanced HCC patients who are eligible for immunotherapy are often diagnosed with imaging tests without tumor biopsy, it is important to develop noninvasive blood-based biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Although tumor tissue-based efficacy biomarkers of immune checkpoint inhibitors (ICIs), such as tumor-infiltrating lymphocyte counts and PD-1/PD-L1 expression, have been reported in a variety of cancer types [ 9 , 10 ], there is no reliable biomarker for predicting the efficacy of combination immunotherapy in HCC. Furthermore, because advanced HCC patients who are eligible for immunotherapy are often diagnosed with imaging tests without tumor biopsy, it is important to develop noninvasive blood-based biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis suggested that high levels of intratumoral and interstitial CD8 + T cells can predict the efficacy of immunotherapy in multiple tumor types, including immunotherapy alone and immunocombination therapy ( Li et al, 2021 ). A phase II study of NSCLC observed that ipilimumab neoadjuvant therapy had significant CD28-dependent activation of both CD4 + T cells and CD8 + T cells ( Yi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs) have aroused wide interest because of its prognostic significance 82 . As an important part of TILs, CD8 T cells have been proved to be associated with lots of immune checkpoint molecules as well as the survival rate of patients 83,84 . However, a pooled analysis 85 containing 3,771 patients showed that increased TILs were not always a positive prognostic factor for breast cancer patients' survival.…”
Section: Sotip Identifies Highly Specific Mecns Associated With Tumor...mentioning
confidence: 99%